Taxonomic review of Berthella and Berthellina (Gastropoda: Pleurobranchoidea) from Brazil, with description of two new species - Juliana Alvim; Alexandre Dias Pimenta (Zoologia (Curitiba), 2015)
ABSTRACT Berthella currently comprises five valid species recorded from the western Atlantic, of which only Berthella agassizii (MacFarland, 1909) and Berthella stellata (Risso, 1826) have been recorded from Brazil. Two species of Berthellina occur in Brazil: Berthellina quadridens (Mörch, 1963) and Berthellina circularis (Mörch, 1863); however, based on a literature review and the anatomical study presented here, we only recognize B. circularis as occurring in the country. This study gives a detailed re-description of B. agassizii, B. stellata and B. circularis based on material from Brazil, and adds two new species to the genus, from the Brazilian coast, Berthella punctata sp. nov. and Berthellina ignis sp. nov. Berthellina circularis and B. quadridens are considered distinct species based on the denticulation of the radular teeth. B. quadridens presents the majority of teeth with two denticles, rarely three-four denticles, while in B. circularis from Brazil the radular teeth are highly denticulate with up to 17 denticles. Berthella and Berthellina do not form a monophyletic group, and cluster in a large polytomy within Pleurobranchidae. A detailed anatomical study is performed to improve the understanding of the evolutionary history of Pleurobranchidae. The comparison with available data on the odontophoric muscles of Pleurobranchoidea shows that Berthella and Berthellina present a pair of the muscle m10v that connects the mj with the ventral portion of the m5, while in Pleurobranchus and Pleurobranchaea the m10v connects the mj with the ventral portion of the m4; Berthella and Berthellina do not present the muscle m10d, which is present in Pleurobranchus and Pleurobranchaea. Based on these characters, Berthella seems to be more closely related to Berthellina than to Pleurobranchus.